Atrial and ventricular tachyarrhythmias in military personnel. Issue 3 (5th August 2015) - Posselt, Bonnie N; Cox, A T; D'Arcy, J; Rooms, M; Saba, M
Abstract : Although rare, sudden cardiac death does occur in British military personnel. In the majority of cases, the cause is considered to be a malignant ventricular tachyarrhythmia, which can be precipitated by a number of underlying pathologies. Conversely, a tachyarrhythmia may have a more benign and treatable cause, yet the initial clinical symptoms may be similar, making differentiation difficult. This is an overview of the mechanisms underlying the initiation and propagation of arrhythmias and the various pathological conditions that predispose to arrhythmia genesis, classified according to which parts of the heart are involved: atrial tachyarrhythmias, atrial and ventricular, as well as those affecting the ventricles alone. It encompasses atrial tachycardia, atrial flutter, supraventricular tachycardias and ventricular tachycardias, including the more commonly encountered inherited primary electrical diseases, also known as the channelopathies. The clinical features, investigation and management strategies are outlined. The occupational impact—in serving military personnel and potential recruits—is described, with explanations relating to the different conditions and their specific implication on continued military service.